Estimated cardiorespiratory fitness and incident risk of cardiovascular disease in China - Yuanjiao Liu; Jinghan Zhu; Ziye Guo; Jiazhou Yu; Xuhui Zhang; Huiqing Ge; Yimin Zhu (BMC, 2023)
Abstract Background Limited evidence is available on the association between estimated cardiorespiratory fitness (e-CRF) and incidence of cardiovascular disease (CVD) in Chinese population. Methods A total of 10,507 adults including 5084 men (48.4%) and 5423 (51.6%) women with a median age of 56.0 (25% quantile: 49, 75% quantile 63) years from the China Health and Retirement Longitudinal Study (CHARLS) was recruited in 2011 as baseline. The CVD incident events were followed-up until 2018. e-CRF was calculated from sex-specific longitudinal non-exercise equations and further grouped into quartiles. Cox proportional models were used to calculate hazard ratio (HR) and 95% confidence interval (CI) for incidence risks of CVD, heart disease and stroke. Results During a median follow-up of 7 years, a total of 1862 CVD, 1409 heart disease and 612 stroke events occurred. In fully adjusted models, each one MET increment of e-CRF was associated with lower risk of CVD (HR = 0.91, 95%CI = 0.85-0.96 for males, HR = 0.87, 95%CI = 0.81-0.94 for females). Compared with the Quartile (Q)1 group, the HRs (95%CI) of the Q2, Q3 and Q4 groups were 0.84 (0.63-1.03), 0.72 (0.57-0.91) and 0.66 (0.51-0.87) for CVD in males. Females had HRs of 0.79 (0.66-0.96) in Q2, 0.71 (0.57-0.88) in Q3 and 0.58 (0.45-0.75) in Q4 for CVD. The associations between e-CRF and heart disease and stroke were slightly weaker than that for CVD in both males and females. Conclusions Higher e-CRF decreases the incident risk of CVD, heart disease and stroke.